Research on hybrid dynamic load balancing algorithm in heterogeneous hierarchical wireless networks - NING Guo-qin1; ZHU Guang-xi1; PENG Lie-xin1; LU Xiao-feng1 (Tongxin xuebao)
A hybrid dynamic load balancing algorithm based on the combination of channel borrowing scheme and load transfer scheme was proposed.The hotspot cells can borrow channels from homogeneous cells with light workload in the compact pattern.At the same time,some ongoing calls can be transferred from hotspot cells into the overlapping hetero-geneous cells with light workload according to certain conditions.The number of borrowed channels and transferred on-going calls per load balancing period was computed by the remainder available channels and new calls arrival rates in the hotspot cell.Simulation results show that the proposed hybrid dynamic load balancing algorithm can decrease the block-ing probabilities,dropping probabilities of hotspot cell system and overall heterogeneous system,the channel utilization of overall heterogeneous system is increased accordingly.